Analisis Struktur dan Kaidah Kebahasaan Teks Eksplanasi pada Berita Online Lampung Geh News Edisi November 2025 - Utami, Dian; Indriani, Julia; Halimah, Supi Nur; Aziza, Sofia Nur; Manik, Tamara Paulina; Fani, Vido Repan Gio; Hastuti, Hastuti (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze the structure and linguistic features of explanatory texts found in the November 2025 edition of Lampung Geh News. The analysis is conducted based on the importance of explanatory texts in presenting information clearly, systematically, and accurately so that readers can understand the phenomena being reported. This research employs a qualitative descriptive method with document analysis techniques applied to selected news articles containing explanatory elements. The results reveal that the explanatory texts in Lampung Geh News fulfill the essential structural components of explanatory writing, namely the identification of phenomena, a sequence of events, and a concluding interpretation. In terms of linguistic features, the texts consistently use chronological and causal conjunctions, action verbs, general nouns, and technical terms relevant to disaster-related phenomena. However, the study also identifies several sections that could be improved, particularly in terms of sentence coherence, to enhance the clarity and flow of information. Overall, the explanatory texts in Lampung Geh News are systematically structured and adhere to the characteristics of explanatory writing, successfully providing readers with clear, informative, and comprehensible explanations of the reported events.